2017
DOI: 10.1007/s11104-017-3439-y
|View full text |Cite|
|
Sign up to set email alerts
|

Severe water deficit restricts biomass production of Lolium perenne L. and Trifolium repens L. and causes foliar nitrogen but not carbohydrate limitation

Abstract: Aims We investigated whether drought-induced impairment of grassland species can be explained directly by plant water deficit or by water-driven limitation of nitrogen (N) and/or carbohydrate sources. Methods In a field experiment, a severe drought treatment was applied on monocultures of Lolium perenne L. (cv. Alligator) (Lp) and Trifolium repens L. (cv. Hebe) (Tr) by using rainout shelters excluding all precipitation, and effects were compared to a rainfed control. Three species-fertiliser treatments were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…In general, these studies have confirmed that a drought-induced water limitation typically leads to a reduction in net primary productivity (NPP;Fuchslueger et al, 2014Fuchslueger et al, , 2016Gherardi and Sala, 2019;Wilcox et al, 2017;Wu et al, 2011). Importantly, however, these studies have also shown that the response of ecosystems to experimental drought can vary quite dramatically (Gherardi and Sala, 2019;Gilgen and Buchmann, 2009;Grant et al, 2014;Hoover et al, 2014;Wilcox et al, 2017). Among others, the drought response of grasslands has been shown to depend on the severity of the experienced drought (Vicca et al, 2012;Wilcox et al, 2017) and important secondary factors, such as the type of grassland affected (Byrne et al, 2013;Gherardi and Sala, 2019;Sala et al, 2015;Wilcox et al, 2017), the intensity of land use (Vogel et al, 2012;Walter et al, 2012), the plant functional composition (Gherardi and Sala, 2015;Hofer et al, 2016Hofer et al, , 2017aMackie et al, 2018) or the biodiversity of an ecosystem (Haughey et al, 2018;Isbell et al, 2015;Kahmen et al, 2005;Wagg et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
“…In general, these studies have confirmed that a drought-induced water limitation typically leads to a reduction in net primary productivity (NPP;Fuchslueger et al, 2014Fuchslueger et al, , 2016Gherardi and Sala, 2019;Wilcox et al, 2017;Wu et al, 2011). Importantly, however, these studies have also shown that the response of ecosystems to experimental drought can vary quite dramatically (Gherardi and Sala, 2019;Gilgen and Buchmann, 2009;Grant et al, 2014;Hoover et al, 2014;Wilcox et al, 2017). Among others, the drought response of grasslands has been shown to depend on the severity of the experienced drought (Vicca et al, 2012;Wilcox et al, 2017) and important secondary factors, such as the type of grassland affected (Byrne et al, 2013;Gherardi and Sala, 2019;Sala et al, 2015;Wilcox et al, 2017), the intensity of land use (Vogel et al, 2012;Walter et al, 2012), the plant functional composition (Gherardi and Sala, 2015;Hofer et al, 2016Hofer et al, , 2017aMackie et al, 2018) or the biodiversity of an ecosystem (Haughey et al, 2018;Isbell et al, 2015;Kahmen et al, 2005;Wagg et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, Arend et al (2016) found a rapid stimulation of photosynthesis immediately after rewetting that continued until the end of the growing season, partly compensating the loss of photosynthetic activity during drought. Hofer et al (2017b) found an increased root mass and increased water-soluble carbohydrate reserves in the stubbles of drought stressed L. perenne at the end of a drought stress period. Both of which could have contribute to increased growth rates observed in their study once rewetting had occurred.…”
Section: Positive Legacy Effects Of Drought Periodsmentioning
confidence: 82%
“…Gutters were installed to prevent the water from flowing onto adjacent plots, and a 0.75 m boarder zone at each plot was not considered for measurements to prevent a possible effect of lateral water flow in the soil. These shelters and plot design had previously been successfully used in other grassland-drought experiments (Hofer et al, 2016(Hofer et al, , 2017a(Hofer et al, , 2017b. Rain-fed controls were subject to the natural precipitation regime.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, mineralization, nitrification, and denitrification were found to be lower under drier environmental conditions [23,24]. Droughts can cause a decrease in microbial biomass N and in N_PU in grasslands [25][26][27][28] and lower soil water content, both leading to a higher concentration of DIN in the soil solution [22]. The effects of drought periods followed by rewetting on the N-cycle vary [29].…”
Section: Introductionmentioning
confidence: 99%